Sand fly fauna of South-Eastern Romania, with the description of Phlebotomus (Transphlebotomus) simonahalepae n. sp. (Diptera: Psychodidae) - Cristina Daniela Cazan (Parasites & Vectors, 2021)
Abstract Background An entomological study was conducted in the Canaraua Fetii Special Protection Area in the Dobrogea region, South-Eastern Romania. Four sand fly species were recorded at this location between 1968 and 1970: Phlebotomus neglectus, Ph. balcanicus, Ph. sergenti and Sergentomyia minuta. The most abundant sand fly species recorded at that time were Ph. balcanicus and Se. minuta. In the context of a countrywide study to update the sand fly species diversity, we surveyed the same area, recording also a previously unknown Ph. (Transphlebotomus) sp., for which we provide a formal description here. Methods Sand flies were collected between July and August in 2018 and 2019 in three sites from Canaraua Fetii, Dobrogea region, Romania. The general aspect of the landscape is of a canyon (vertical, narrow walls and deep valleys). Species identification was done using both morphological and molecular analyses. Results Out of 645 collected sand flies, 644 (99.8%) were morphologically identified as Ph. neglectus, while one female specimen (0.2%) was assigned to a previously unknown species, belonging to the subgenus Transphlebotomus. The morphological and molecular examination of this specimen showed that it is a previously unknown species which we formally describe here as Phlebotomus (Transphlebotomus) simonahalepae n. sp. Also, Ph. balcanicus, Ph. sergenti, and Se. minuta (previously recorded in this location) were not present. Conclusions The study revealed for the first time the presence of sand flies of the subgenus Transphlebotomus in Romania. Moreover, a new species, Ph. simonahalepae n. sp., was described based on a female specimen, raising the number of species in this subgenus to six. In the investigated natural habitat, the predominant species was Ph. neglectus instead of Ph. balcanicus and Se. minuta (recorded as the predominant species in 1968–1970). Graphical abstract